Depression, Anxiety, Coping Strategies and Quality of Life of the Elderly During the Covid-19 Pandemic - Iswatun Iswatun; Ah. Yusuf; Joko Susanto; Makhfudli Makhfudli; Abd. Nasir; Amellia Mardhika (International Journal of Public Health Science (IJPHS), 2022)
Background and aims. Covid-19 is currently a global health problem, with the spread and transmission to the population almost all over the world. This has a psychological impact on the elderly which will affect mental health and quality of life. This study aims to identify the relationship of depression, anxiety, coping strategies with the quality of life of the elderly during the covid-19 pandemic in Lamongan. Method and materials. This study uses a cross sectional design, the population is all the elderly in the Lamongan area. The sampling technique used cluster sampling technique, with a total sample of 232 respondents. The independent variables are depression, anxiety and coping strategies, while the dependent variable is the quality of life of the elderly. Instruments for depression used the Geriatric Depression Scale (GDS 15), anxiety using the Geriatric Anxiety Inventory (GAI) and quality of life using the WHOQOOL-BRIEF questionnaire. Data were analyzed using the Multiple linear regression test.Result. The results showed that there was a relationship between depression and quality of life (ρ=0.001), there was a relationship between anxiety and quality of life (ρ=0.000) and there was also a relationship between coping strategies and quality of life (ρ=0.027). Conclusion. The study provides important information about the psychological impact of developing appropriate psychological interventions to improve mental health and quality of life, especially for at-risk groups, especially the elderly.